4‐Nitrophenol exposure alters the AhR signaling pathway and related gene expression in the rat liver. Issue 2 (12th May 2016) - Li, Ruonan; Song, Meiyan; Li, Zhi; Li, Yansen; Watanabe, Gen; Nagaoka, Kentaro; Taya, Kazuyoshi; Li, Chunmei
Abstract: 4‐Nitrophenol (PNP) is well known as an environmental endocrine disruptor. The aim of this study was to clarify the mechanism of PNP‐induced liver damage and determine the regulatory involvement of the aryl hydrocarbon receptor (AhR) signaling pathway and associated gene expression. Immature male Wistar–Imamichi rats (28 days old) were randomly divided into control and PNP groups, which consisted of 1‐ and 3‐day exposure (1 DE and 3 DE, respectively) and 3‐day exposure followed by 3‐day recovery (3 DE + 3 DR), groups. Each group was administered the vehicle or PNP (200 mg kg –1 body weight). The body and liver weight were significantly decreased in the 3 DE group. The mRNA expression levels of estrogen receptor‐α (ERα), glutathione S‐transferase (GST) and AhR exhibited a significant increase in the 1 DE group whereas, in contrast, that of cytochrome P450 (CYP) 1A1 decreased significantly in the 3 DE +3 DR group. AhR and CYP1A1 proteins were detected in the cytoplasm of hepatocytes of the 1 DE and 3 DE +3 DR groups whereas the ERα protein was found in the hepatocyte nuclei of the 1 DE and 3 DE groups. The present study demonstrates that PNP activated the AhR signaling pathway and regulated related CYP1A1 and GST gene expression in the liver. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : 4‐Nitrophenol (PNP) is an environmental endocrine disruptor. The aim of this study was to clarify the mechanism of PNP‐induced liver damage. 28‐day‐old male Wistar‐Imamichi rats were randomly divided into control (vehicle) and PNP (200 mg·body‐ 1 weight) groups, which consisted of 1‐ and 3‐day exposure (1 DE and 3 DE, respectively) and 3‐day exposure followed by 3‐day recovery (3 DE + 3 DR), groups. The body and liver weight were significantly decreased in the 3 DE group. The mRNA expression levels of estrogen receptor‐α (ERα), glutathione S‐transferase (GST), and aryl hydrocarbon receptor (AhR) exhibited a significant increase in the 1 DE group while cytochrome P450 (CYP) 1A1 decreased significantly in the 3 DE +3 DR group. AhR and CYP1A1 proteins were detected in the cytoplasm of hepatocytes of the 1 DE and 3 DE +3 DR groups while the ERα protein was found in the hepatocyte nuclei of the 1 DE and 3 DE groups. The present study demonstrates that PNP activated the AhR signaling pathway and regulated related CYP1A1 and GST gene expression in the liver.